2023
DOI: 10.3390/nu15204405
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Acne and Rosacea Patients—A Controlled Study and Comprehensive Analysis

Anne Guertler,
Arina Volsky,
Quirine Eijkenboom
et al.

Abstract: As the relationship between exposome factors and inflammatory skin diseases is gaining increasing attention, the objective of this study was to investigate dietary patterns among acne and rosacea patients and to establish the disease risk attributable to nutrition. In this cross-sectional, controlled study, patients’ dietary habits were assessed via subjective ratings of beneficial and trigger foods, followed by standardized food frequency surveys (FFS). Scores for disease-specific risk stratification based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Recent research has shown that individuals with rosacea were able to identify dietary triggers more easily than beneficial foods [53]. Supporting previous data, alcohol, spices, sugar, and fried foods were perceived as leading dietary triggers, and the foods most frequently mentioned as favorable in the present cohort were high in dietary fiber, including vegetables, fruits, whole grains, and beans.…”
Section: Discussionsupporting
confidence: 88%
“…Recent research has shown that individuals with rosacea were able to identify dietary triggers more easily than beneficial foods [53]. Supporting previous data, alcohol, spices, sugar, and fried foods were perceived as leading dietary triggers, and the foods most frequently mentioned as favorable in the present cohort were high in dietary fiber, including vegetables, fruits, whole grains, and beans.…”
Section: Discussionsupporting
confidence: 88%
“…These include vegetables, fruits, herbs, spices, fiber, n-3 PUFA, MUFA, magnesium, flavonoids and carotenoids. They also reduced the severity of acne by limiting sebum production [37,38], whereas SFA, trans fatty acids, high GI carbohydrates, high omega-6/omega-3 PUFA ratio, meat, cheese and alcohol consumption were associated with increased inflammation [39] and worsened skin conditions [27,37]. Therefore, the dietary plan prepared for this study did not include dairy products or industrially processed products.…”
Section: Discussionmentioning
confidence: 99%
“…in chocolate products [71]. Dark chocolate is known to be abundant in phenolic antioxidants, principally flavonoids, which were repeatedly demonstrated to have a preventive effect in the prevention of cardiovascular disease and diabetes, but a growing number of studies suggest that chocolate intake is associated with the progression of acne vulgaris among adolescents [72][73][74][75][76][77]. Theses were proposed to clarify the potential impact of chocolate intake on acne symptoms.…”
Section: Chocolatementioning
confidence: 99%